Advancements in Tobacco (Nicotiana tabacum L.) Seed Oils for Biodiesel Production - Wu, Shengjiang; Gao, Chuanchuan; Pan, Hu; Wei, Kesu; Li, Delun; Cai, Kai; Zhang, Heng (Frontiers in Chemistry, 2022)
With the increasing demand for fossil fuels, decreasing fossil fuel reserves and deteriorating global environment, humanity urgently need to explore new clean and renewable energy to replace fossil fuel resources. Biodiesel, as an environmentally friendly fuel that has attracted considerable attention because of its renewable, biodegradable, and non-toxic superiority, seems to be a solution for future fuel production. Tobacco (Nicotiana tabacum L.), an industrial crop, is traditionally used for manufacturing cigarettes. More importantly, tobacco seed is also widely being deemed as a typical inedible oilseed crop for the production of second-generation biodiesel. Advancements in raw material and enhanced production methods are currently needed for the large-scale and sustainable production of biodiesel. To this end, this study reviews various aspects of extraction and transesterification methods, genetic and agricultural modification, and properties and application of tobacco biodiesel, while discussing the key problems in tobacco biodiesel production and application. Besides, the proposals of new ways or methods for producing biodiesel from tobacco crops are presented. Based on this review, we anticipate that this can further promote the development and application of biodiesel from tobacco seed oil by increasing the availability and reducing the costs of extraction, transesterification, and purification methods, cultivating new varieties or transgenic lines with high oilseed contents, formulating scientific agricultural norms and policies, and improving the environmental properties of biodiesel.